Expert review on conceptual design model of assistive courseware for low vision (AC4LV) learners - Aziz, Nurulnadwan; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (WAIRCO Journal Publishers, 2015)
— This paper reports an ongoing project regarding the development of Conceptual Design Model of Assistive Courseware for Low Vision (AC4LV) learners. Having developed the intended model, it has to be validated prior to produce it as guidance for the developers to develop an AC4LV. This study requires two phases of validation process which are through expert review and prototyping method.This paper presents a part of the validation process which is findings from experts review on Conceptual Design Model of AC4LV which has been carried out through questionnaire.Results from 12 international and local experts from various respectable fields in Human Computer Interaction (HCI) were discussed and justified.In a nutshell, reviewed Conceptual Design Model of AC4LV was formed. Future works of this study is to validate the reviewed model through prototyping method prior to test it to the targeted users.